PENGARUH PEMBIAYAAN MURABAHAH, INTELLECTUAL CAPITAL, DAN ZAKAT TERHADAP KINERJA KEUANGAN BANK SYARIAH - Fatih, Faiz Al; Hatmoko, Haryo Wahyu; Sunarmo, Agus; Faturokhman, Agus (Jurnal Riset Akuntansi Soedirman, 2024)
This study aims to investigate the influence of murabaha financing, intellectual capital, and zakat on the financial performance of Islamic commercial banks in Indonesia, proxied by Return on Assets (ROA), during 2017-2019. Using secondary data from the annual financial reports of 12 Islamic banks listed by the Financial Services Authority (OJK), the analysis was conducted with multiple linear regression methods. The findings reveal that murabaha financing and intellectual capital significantly influence financial performance, indicating their critical roles in enhancing profitability and operational efficiency. However, zakat was found to have no significant impact on financial performance despite its importance as a manifestation of social responsibility. This study highlights practical implications for Islamic banks to optimize murabaha financing management, develop intellectual capital, and enhance transparency in zakat management to build public trust. Recommendations for regulators include providing incentives for zakat-active banks and encouraging integrated zakat reporting. Future